Founding an adverse drug reaction (ADR) network: A method for improving doctors spontaneous ADR reporting in a general hospital. (19th August 2013) - Goldstein, Lee Hilary; Berlin, Maya; Saliba, Walid; Elias, Mazen; Berkovitch, Matitiyahu
Abstract Adverse drug reactions (ADR) are underreported by doctors despite numerous efforts. We aimed to determine if establishing an "ADR reporting doctor's network" within a hospital would increase the quantity of ADRs reported by hospital doctors. One hundred hospital doctors joined the network. Email reminders were sent to network members during the 1 year study period, conveying information about ADRs reported, amusingly and pleasantly reminding them to report ADRs in minimal detail, by phone, email, text message or mail to the Clinical Pharmacology Unit, who would further complete the report. A total of 114 ADRs were reported during the study period in comparison to 48, 26, and 17 in the previous 3 years (2008, 2009, 2010, respectively). In the 3 years prior, doctors reported 41.7% of the reported ADRs whereas in the study period, doctors reported 74.3% of ADRs (P < .001), reflecting an 80% increase in doctors reports. Ninety seven percent of doctors' reports were of ADR network members. Thirty‐four (34%) network members reported an ADR during the study period and 31 of the 34 reporters had never reported ADRs before becoming network members. Establishing an ADR network of doctors substantially increases ADR reporting amongst its members.